DEVELOPMENT AND VLAIDATION OF SIMPLE UV-SPECTROPHOTOMETRIC METHOD OF QUANTIZATION OF DIAZEPAM IN BULK DRUG AND SOLID DOSAGE FORMULATION USING MIXED SOLVENCY CONCEPT - Jain, Sanjay; Maheshwari, R. K.; Nema, R. K.; Singhvi, Indrajeet (International Journal of Current Pharmaceutical Research, 2017)
Objective: Commonly used organic solvents for spectrophotometric analysis of water insoluble drugs are methanol, ethanol, chloroform, benzene, toluene etc. The main drawbacks of organic solvents include high cost, toxicity, and pollution. Organic solvents have numerous adverse effects caused by single exposure like dermatitis, headache, drowsiness, nausea, eye irritation and long term exposure causes serious effects such as neurological disorder, chronic renal failure, and liver damage. They should be replaced by other ecofriendly alternative sources. Methods: The present study is an attempt to show that solid can also be used to act as solvent precluding the use of organic solvents. A simple, safe and sensitive method of spectrophotometric determination of diazepam obeyed beers law in the concentration range of 5-25 mcg/ml at 306 nm. Results: The results of analyses have been validated statistically for Linearity, accuracy, precision, LOD and LOQ. The results of validation parameters also indicated that proposed method was found to be accurate, precise, reproducible, sensitive, and suitable for routine quality control analysis for estimation of diazepam in bulk drug and solid dosage formulation. Conclusion: A rapid, simple, and non toxic UV spectrophotometric method has been developed for the determination and quantification of diazepam. The present method also validated as per ICH guidelines for linearity, precision, accuracy.